2020
DOI: 10.3390/app10072542
|View full text |Cite
|
Sign up to set email alerts
|

Many-Body Effects in FeN4 Center Embedded in Graphene

Abstract: We introduce a computational approach to study porphyrin-like transition metal complexes, bridging density functional theory and exact many-body techniques, such as the density matrix renormalization group (DMRG). We first derive a multi-orbital Anderson impurity Hamiltonian starting from first principles considerations that qualitatively reproduce generalized gradient approximation (GGA)+U results when ignoring inter-orbital Coulomb repulsion U ′ and Hund exchange J. An exact canonical transformation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 100 publications
(118 reference statements)
0
8
0
Order By: Relevance
“…In this instance, we deployed GGA+ U calculations for capturing the strong interactions from the 3d– and 5d–electron transition metals. For the 3d–electron TMs, we obtained the Hubbard U value from the literature. However, after thorough testing we identified that total energies, bond lengths, and the magnetic moment of the TM–N 4 –C (TM = Co, Fe, and V) structures with the appropriate U are similar to calculations with U = 0. Hence, we have concluded that a plain DFT approach is sufficient for our calculations.…”
Section: Methodsmentioning
confidence: 96%
“…In this instance, we deployed GGA+ U calculations for capturing the strong interactions from the 3d– and 5d–electron transition metals. For the 3d–electron TMs, we obtained the Hubbard U value from the literature. However, after thorough testing we identified that total energies, bond lengths, and the magnetic moment of the TM–N 4 –C (TM = Co, Fe, and V) structures with the appropriate U are similar to calculations with U = 0. Hence, we have concluded that a plain DFT approach is sufficient for our calculations.…”
Section: Methodsmentioning
confidence: 96%
“…M. Sajjad et al reported that polar nitrogenated holey graphene shows a superior anchoring of NaPSs [ 29 ]. Additionally, the co-doped graphene/carbon nanostructures are also reported to be intensively attractive, due to their novel geometries and properties [ 31 , 32 , 33 , 34 , 35 ]. For example, G. Xia et al reported that N and O co-doped porous carbon nanofibers could effectively alleviate the “shuttling effect” via adsorbing NaPSs by strong chemical interactions [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such an approach has been used in previous studies of MIL-101 materials [23][24][25][26][27] and other Fe-containing organometallics [20][21][22]. Beyond the van der Waals materials, cluster models have been successfully applied for the optimization of reduction activity of covalently bonded Fe-N4@graphene for fuel-cell fabrication [28][29][30]. In our work, this technique successfully unravels the mechanism of redox reactions in this MOF and opens a pathway for identifying irreversible Li intercalation reactions.…”
Section: Introductionmentioning
confidence: 94%